Implementasi Peraturan Bupati Mandailing Natal Nomor 7 Tahun 2016 Dalam Rangka Pengembangan Wirausaha Masyarakat di Desa Padang Bulan Kecamatan Kotanopan - Rahmad Kurniawan; Dedi Amrizal (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
This research was conducted in Padang Bulan village, Kec. Kotanopan, Kab.Mandailing Natal. The purpose of this study was to find out how the implementation of the Mandailing Natal Regent Regulation Number 7 of 2016 in the context of developing community entrepreneurs in Padang Bulan village, Kotanopan sub-district. The type of research used is a descriptive method with qualitative data analysis, namely the method used to dissect a phenomenon and event by describing it into sentences and language based on the findings in the field. Based on the results of the research that the author did, it is known that the Mandailing Natal Regent Regulation Number 7 of 2016 in the Context of Community Entrepreneurial Development in Padang Bulan Village, Kotanopan District has been implemented but not optimally. This can be seen through research categorizations such as the program being implemented but not yet optimal due to the Covid-19 pandemic. the current target to be achieved by the government has made efforts to approach and interact with the community in collaboration and cooperation in improving entrepreneurial development. However, this is hampered by the Covid-19 virus that has hit Indonesia, which has paralyzed all social activities, and the supervision of policies issued. Currently, the supervision carried out by the village government and in collaboration with other institutions has been carried out. This supervision is carried out from material production to product marketing. However, in the field there are still many business units that still need special attention and handling from the related units because there is still a lack of concern for entrepreneurial development in Padang Bulan village but supervision in the village is still weak, there is interaction between the village government and the community so far the government The village has carried out socialization and counseling activities in terms of developing community entrepreneurship. However, this activity did not last long, due to the Covid-19 pandemic.Â